2021
DOI: 10.3389/ijph.2021.1604073
|View full text |Cite
|
Sign up to set email alerts
|

Change in Colorectal Cancer Tests Submitted for Reimbursement in Switzerland 2012–2018: Evidence from Claims Data of a Large Insurance

Abstract: Objectives: Guidelines recommend colorectal cancer (CRC) screening by fecal occult blood test (FOBT) or colonoscopy. In 2013, Switzerland introduced reimbursement of CRC screening by mandatory health insurance for 50-69-years-olds, after they met their deductible. We hypothesized that the 2013 reimbursement policy increased testing rate.Methods: In claims data from a Swiss insurance, we determined yearly CRC testing rate among 50-75-year-olds (2012–2018) and the association with socio-demographic, insurance-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Second, our claims data omitted inpatient tests. We had earlier estimated in another claims dataset that between 3.5 and 5% of colonoscopies in Switzerland are performed on inpatients ( Schneider et al, 2021 ). When conducting additional estimations with this data, we found that in Uri, inpatient colonoscopies accounted for 7.4% of colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…Second, our claims data omitted inpatient tests. We had earlier estimated in another claims dataset that between 3.5 and 5% of colonoscopies in Switzerland are performed on inpatients ( Schneider et al, 2021 ). When conducting additional estimations with this data, we found that in Uri, inpatient colonoscopies accounted for 7.4% of colonoscopies.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a clear socioeconomic gradient in colorectal cancer testing in Switzerland, with lower screening by younger citizens with high-deductible health plans [6,12]. We found that those participating in the screening programme were younger and healthier and had higher-deductible plans than those tested outside the programme.…”
Section: Discussionmentioning
confidence: 44%
“…They were (c) up to date with colonoscopy if they had undergone any colonoscopy in 2010-2018 and no faecal occult blood test in 2017-2018. Data were extracted from the Swiss Health Survey for comparison, using the methods described in a recent publication [12].…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the Helsana Group covers about 15% of the Swiss population from all patient groups and Swiss regions. Previous studies showed that the population is largely representative for the general population of Switzerland, and that feasibility testing based on this data is appropriate [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%